2013
DOI: 10.1021/jp310534x
|View full text |Cite
|
Sign up to set email alerts
|

Anomeric Effect in Halogenated Methanols: A Quantum Theory of Atoms in Molecules Study

Abstract: The quantum theory of atoms in molecules (QTAIM) has been used to analyze the gauche conformational preference of fluoromethanol and chloromethanol. The analysis of the total atomic population and localization and delocalization indices show trends that are not in line with the hyperconjugative explanation. Energy terms arising from the QTAIM partitioning have been obtained for fluoromethanol, revealing that (i) C-O interaction plays the most significant role in stabilizing the gauche rotamer and (ii) the summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…This is a robust topological energy partitioning method that disentangles the total energy of a system into intra-and interatomic contributions of various types. IQA is inspired by earlier work [23] and has been used by several groups to study a wide variety of interactions and phenomena, including but not limited to: halogen-halogen interactions in perhalogenated ethanes [24], halogen bond formation [25], conformational analysis of diheteroaryl ketones and thioketones [26], proton transfer reactions [27], formation of an intramolecular bond path between two electronegative atoms [28], substituent effects in electronically excited states [29], cooperative and anti-cooperative effects in resonance-assisted hydrogen bonds in malondialdehyde [30], short-range electrostatics in torsional potentials [31], new insights in atomatom interactions for future drug design [32], the anomeric effect in halogenated methanols [33], hydrogen-hydrogen interaction in planar biphenyl [34], the steric repulsion in congested molecules [35], charged hydrogen-bonded complexes [36], trapping of CO 2 by adduct formation [37], and the diastereoselective allylation of aldehydes [38].…”
Section: Introductionmentioning
confidence: 99%
“…This is a robust topological energy partitioning method that disentangles the total energy of a system into intra-and interatomic contributions of various types. IQA is inspired by earlier work [23] and has been used by several groups to study a wide variety of interactions and phenomena, including but not limited to: halogen-halogen interactions in perhalogenated ethanes [24], halogen bond formation [25], conformational analysis of diheteroaryl ketones and thioketones [26], proton transfer reactions [27], formation of an intramolecular bond path between two electronegative atoms [28], substituent effects in electronically excited states [29], cooperative and anti-cooperative effects in resonance-assisted hydrogen bonds in malondialdehyde [30], short-range electrostatics in torsional potentials [31], new insights in atomatom interactions for future drug design [32], the anomeric effect in halogenated methanols [33], hydrogen-hydrogen interaction in planar biphenyl [34], the steric repulsion in congested molecules [35], charged hydrogen-bonded complexes [36], trapping of CO 2 by adduct formation [37], and the diastereoselective allylation of aldehydes [38].…”
Section: Introductionmentioning
confidence: 99%
“…Ferro‐Costas, Vila, and Mosquera (F‐CVM) have recently demonstrated that the anomeric effect in halogen‐substituted methanols cannot be explained by hyperconjugation arguments based on the behavior of atomic populations and the QTAIM localization/delocalization indices. These authors have presented lower‐triangular matrix‐like tabulations of the delocalization indices and have used differences between these matrices in their argumentation …”
Section: Localization/delocalization Matrices (Ldm) Delocalization Mmentioning
confidence: 99%
“…Disregarding the nature of the matrix elements, the form of the matrices used by (F‐CVM) is identical to the oft‐used graph‐theoretical connectivity (adjacency) matrices. Connectivity matrices have been brought from the field of graph theory, a branch of pure mathematics, to mathematical chemistry by scientists such as Balaban, Gutman, Hosoya, Nicolić, Randić, Trinajstić, and several others .…”
Section: Localization/delocalization Matrices (Ldm) Delocalization Mmentioning
confidence: 99%
“…[1] While a-fluoroalcohols have been studied extensively by computational methods, [2] complementary experimental studies are lacking,a nd several attempts to prepare them have been unsuccessful. Heptafluorocyclobutanol was obtained in quantitative yield from hexafluorocyclobutanone by HF addition in anhydrous hydrogen fluoride.T he compound was characterized by its X-rays ingle crystal structure.H eptafluorocyclobutanol readily undergoes hydrolysis to hexafluorocyclobutane-1,1-diol, whichw as also structurally characterized by X-ray diffraction.…”
mentioning
confidence: 99%
“…[1] While a-fluoroalcohols have been studied extensively by computational methods, [2] complementary experimental studies are lacking,a nd several attempts to prepare them have been unsuccessful. [1] While a-fluoroalcohols have been studied extensively by computational methods, [2] complementary experimental studies are lacking,a nd several attempts to prepare them have been unsuccessful.…”
mentioning
confidence: 99%